Neuroprotection in Synaptic Signalling During Neurological Disorders - Otero losada, Matilde Estela (2021)
Some of the most devastating and costly conditions in the world arise from neurological andneurodegenerative disorders. About one-third of the world's population suffers from neurologicaldiseases, including Parkinson's (PD) and Alzheimer's (AD) diseases, multiple sclerosis, epilepsy, spinal cord injury, and others. Symptoms may show early in childhood or substantially delayedin adolescence or young adulthood. Animal models are powerful tools aiding in understandingneurological pathophysiology towards developing neuroprotective strategies.So far, there are no well-established treatments for brain repair. Hence, neuroprotectionbecomes imperative. Synapses pose major targets for finding new neuroprotective agents.The aimof this topic is to share research addressing neuroprotective strategies for the brain, theirpossible pathways, and the use of pharmacological analogues. Four reviews are about hypoxia. Twochapters address themolecular bases of cognitive impairment in AD. Biochemical and physiologicalaspects of neuroprotective agents focusing on synaptic modifications, neuroprotection followingperinatal asphyxia, and pharmacological- and genetic-targeting strategies for Alzheimer's and Parkinson's diseases are reviewed.